Knowing as Holistic Experience: A Challenge to Plato from Jungian Sandplay - Donald, Beatrice (Paideusis, 2008)
Plato’s suggestion that pure knowledge, described in his theory of Forms as the archetypal basis of reality, is questioned using the sequence from the key session of a Jungian Sandplay therapy case as an example of direct human experience of the archetype. As was recognized by Jung, a parallel may be drawn between Jungian archetypes and Platonic Forms in that both are primary structures contained and manifested in the phenomenal world. In Sandplay, a patient unable to transcend her quandary through reason is able to find relief from the tension of the arguing opposites within her when she creates an image with her hands, in a state of reverie, responding to an internal impetus governed not by reason alone but by spontaneous, nonverbal sensory experience. The image she creates in this way brings her into a deep relationship with herself and marks the beginning of a newly forming selfconfidence that guides her. This example illustrates the holistic nature of human experience and change processes, in therapy or in any learning context.